Kata Budaya sebagai Identitas Nigeria dalam Novel ‘Amāliqat al-Shimāl Karya Najīb al-Kīlānī - Silmi Malina Binta (Al-Ma‘rifah, 2021)
The word culture is a word that contains solid cultural elements of a particular group or area. This word cannot be understood directly without any knowledge or explanation. This study includes an analysis of the word culture with the material object of the historical novel ‘Amāliqat al-Shimāl by Najīb al-Kīlānī. The word culture contained in the novel was collected, then included in each category based on the division of the cultural elements of Peter Newmark. The method used is descriptive qualitative by presenting the data in the analysis. The cultural words analyzed are given a general and concise explanation accompanied by pictures. This study aims to understand the novel’s content and strengthen the word culture, which is found as the Nigerian identity, which is the background of the events in the novel. The study results found 21 cultural words that have an identical effect on Nigeria. The cultural words are detailed in several subcategories, including one animal name, one plant name and eight place names in the ecological culture category, one name for traditional clothing in the material culture category, five names of state figures in social culture, and two names of beliefs, and three names of ethnic groups in the variety of social organization cultures.